Biodiversity of Spiders from Banana Fields of District Matiari, Sindh, Pakistan - Kaka, Shadab; Ursani, Tahira Jabeen; Khokhar, Jawaid; Malik, Samina (Dialogue Social Science Review (DSSR), 2025)
Biodiversity applied for diverse life forms existing in the globe. Here it means coexistence of spiders with banana plantations which was observed very affluent in the fields of banana located in the District Matiari. Total 992 specimens (including spiderlings) were assembled. The period of this research was from the month of January to October 2021 and January to May 2022. Spider biodiversity is was notice high because of the preferred environmental (Biotic: plantations; vegetation, prey etc and abiotic: temperature and humidity) circumstances. Present work is focused on the biodiversity of spiders from banana Agro-ecosystem of District Matiari. It is one of the most fertile agricultural districts of Sindh. Mostly the livelihood of the people of Matiari district depends upon the agriculture; hence many crops are being grown here. The banana (Musa paradidica L.) belongs to the family Musaceae is the major fruit crop of Sindh.. During field survey from frequently banana growing taluka’s (Hala, New Saeedabad and Matiari). During this study six families are identified namely; Araneidae, Lycosidae, Oxyopidae, Tetragnathidae, Salticidae and Gnaphosidae. These families were classified on the basis of their web-building and predation methods.